A rare case of adult colocolonic intussusception of the descending colon. Issue 11 (24th November 2019) - Taher, Randa; Kopelman, Yael; Younis, Aurwa; Sheffer, Daniel
Abstract : A 28-year-old woman approached the emergency department because of recent diffuse abdominal pain and diarrhoea. Peritoneal signs on physical exam led to abdominal CT scan which demonstrated colonic obstruction, resulting from colocolonic intussusception of the descending colon. An exploratory laparotomy confirmed the diagnosis as well as the aetiology of a 4 cm intraluminal polyp. Left hemicolectomy with primary anastomosis was performed. The final pathology revealed a tubulovillous adenoma with multiple foci of high-grade dysplasia. Intussusception is a rare cause for colonic obstruction, and ~90% of cases in adults are secondary to an anatomical or pathological condition. Therefore, we recommend oncological resection of the affected part.